Fracking, Wars and Stock Market Crashes: The Price of Oil During the Great Recession - GarzÃ³n, Antonio J.; Hierro, Luis Ã. (International Journal of Energy Economics and Policy, 2018)
This study analyses how oil prices have been affected by three types of events that took place during the Great Recession: the development of fracking, wars in Libya, Syria and Ukraine and the stock market crash of 2008. To do this, we employ co-integration analysis, using a vector error correction model (VECM) for a period spanning August 2007 to August 2016. The principal results obtained are: firstly, that including a variable to represent the increase in production associated to fracking in the US improves the model’s long term estimation, as it embraces a new variable co-integrated in the long term; secondly, that the wars in Libya and Ukraine only influenced prices indirectly, insofar as the former sparked a reduction in OPEC production and the latter an increase in OECD oil reserves, both short term; and thirdly, that the stock market crash of 2008 led to a short- term reduction in oil prices. Keywords: Great Recession, oil prices, fracking, stock market crash, war. JEL Classifications: Q4, Q43